Recent progress in the development of DNA-based biosensors integrated with hybridization chain reaction or catalytic hairpin assembly - Mo, Liuting; He, Wanqi; Li, Ziyi; Liang, Danlian; Qin, Runhong; Mo, Mingxiu; Yang, Chan; Lin, Weiying (Frontiers in Chemistry, 2023)
As isothermal, enzyme-free signal amplification strategies, hybridization chain reaction (HCR), and catalytic hairpin assembly (CHA) possess the advantages such as high amplification efficiency, excellent biocompatibility, mild reactions, and easy operation. Therefore, they have been widely applied in DNA-based biosensors for detecting small molecules, nucleic acids, and proteins. In this review, we summarize the recent progress of DNA-based sensors employing typical and advanced HCR and CHA strategies, including branched HCR or CHA, localized HCR or CHA, and cascaded reactions. In addition, the bottlenecks of implementing HCR and CHA in biosensing applications are discussed, such as high background signals, lower amplification efficiency than enzyme-assisted techniques, slow kinetics, poor stability, and internalization of DNA probes in cellular applications.